THE INFLUENCE OF TA'LIM ASSEMBLY ACTIVITIES ON THE MATURITY OF RELIGIOUS ATTITUDES OF THE ELDERLY IN THE ENVIRONMENT OF RW 05 BABAKAN DUSUN BANDUNG SITURAJA - Endang Muslim; Muhammad Yusuf (STAI Sebelas April Sumedang, 2022)
The Ta'lim Council activities are a place of teaching or recitation for people who study the teachings of the Islamic religion. Likewise, the ta'lim assembly is a means of increasing public knowledge and even solving life problems experienced with religious teachings and can improve the morals and morals of its congregation to realize grace for the universe. This research aims to determine: 1) Activities of the Ta'lim Assembly in RW 05 Hamlet Babakan Bandung Situraja 2) Maturity of Religious Attitudes of the Elderly in the Neighborhood of RW 05 Hamlet Babakan Bandung Situraja 3) Influence of the Activities of the Ta'lim Assembly on the Maturity of Religious Attitudes of the Elderly in RW 05 Babakan Hamlet Bandung Situraja. This research uses a quantitative research approach. This research is a non-experimental type, namely correlation research. By collecting observation data, documentation, questionnaires. Observations and documentation were carried out on matters related to the activities of the ta'lim assembly in RW 05 Hamlet Babakan Bandung Situraja and questionnaires were carried out to elderly mothers aged 60 years and over regarding the maturity of the elderly's religious attitudes. Based on the research results, it can be concluded that the results of this research prove that there is a high or good influence between the activities of the ta'lim assembly on the maturity of the religious attitudes of the elderly. And there is also a positive and significant relationship, which means that the better the activities of the Ta'lim Council, the higher the maturity of the religious attitudes of the elderly in RW 05 Hamlet Babakan Bandung Situraja.